Upper Paleolithic and preventive Archaeology in Portugal: challenges and opportunities. - Gameiro, Cristina (2018)
In the last 20 years, Palaeolithic archaeology in Portugal has produced some of the most revolutionary and important sites in the world (e.g., Côa Valley Palaeolithic rock art; Lagar Velho child-burial and the 400,000-year-old human skull from Aroeira cave) nonetheless, a hiatus visible the map of geographical distribution of these sites is obvious and means nothing but the lack of research and not the absence of human habitation in the past. Nevertheless, some new important Palaeolithic sites have been recently identified during preventive archaeological works. We will present new data concerning these new sites and a framework for a program that can help archaeologists working in preventive archaeology to ensure faster identification of sites, improving performance of archaeological interventions and reducing the economic impact for developers.